MD&A Quality as Measured by the SEC and Analysts' Earnings Forecasts* - BARRON, ORIE E.; KILE, CHARLES O.; O'KEEFE, TERRENCE B. (Contemporary Accounting Research, 1999)
Abstract This study examines the predictive value of Management Discussion and Analysis (MD&A) information. More specifically, this study tests the association between properties of analysts' earnings forecasts and MD&A quality, where MD&A quality is measured by the Securities Exchange Commission (SEC). We find that high MD&A ratings are associated with less error and less dispersion in analysts' earnings forecasts after controlling for many other expected influences on analysts' forecasts. We also find that estimated regression coefficients are consistent with MD&A information having a substantial effect on earnings forecasts. Finally, we find our results are driven by forward‐looking disclosures about capital expenditures and operations, and also by historical disclosures about capital expenditures. These findings are consistent with the suggestion by many constituencies (including the SEC) that the type of information found in high quality MD&A is particularly relevant for predicting earnings.